AI-Based Marketing Strategy Analysis - Taking "Liulishuo" as an Example - Xu, Shupeng (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of artificial intelligence (AI) technology, mobile education products are playing an increasingly important role in the education industry. In the field of mobile learning, through AI technology and personalized learning models, products such as Baicizhan and "Liulishuo" have achieved success, providing students with a more flexible and convenient learning method. This article takes China’s online English education brand "English Liulishuo" as the research object and explores its marketing strategy through the SWOT analysis method. The article pointed out that with the rise of mobile education products, Liulishuo, as a representative company, has achieved success in the market, but it also faces challenges such as revenue losses and negative news. Through SWOT analysis, it was found that Liulishuo’s advantages outweighed its disadvantages, but there was still room for improvement. Companies are advised to exploit global English learning demand, technological advancements, and collaborations to develop new markets. The study emphasizes the importance of SWOT analysis, fills the relevant research gaps, and is of great significance to the development of similar platforms. Finally, the article points out that the understanding of operational data needs to be deepened to more comprehensively evaluate the effectiveness of brand promotion. SWOT analysis provides enterprises with scientific evaluation and strategic selection methods, helping enterprises to succeed in the fiercely competitive market.